Manifestações otoneurológicas em indivíduos infectados pelo HTLV-1 assintomáticos e com mielopatia: estudo comparativo - Ludimila Labanca (2012)
INTRODUCTION: Inflammatory manifestations are characteristic of the Human T-lymphotropic virus type 1 (HTLV-1)/ associated myelopathy/ tropical spastic paraparesis (HAM/TSP), which can affect the vestibulospinal tract and could be the explanation for the higher frequency of otoneurological manifestations described in HAM/TSP. However, this finding has not been systematically studied, so far. OBJETIVE: To compare the frequency of otoneurological manifestations in individuals infected with HTLV-1 that are asymptomatic and with HAM/TSP. METHODOLOGY: The participants of this study are included in the cohort of the Interdisciplinary Group of HTLV Researches GIPH, started at 1997 and with 637 ex-blood donors infected by HTLV-1 and 232 blood donors (controls) enrolled in the cohort at the moment of this analysis. The present study is a sectional evaluation of 120 individuals of the cohort, 60 of whom were infected with HTLV-1 (30 asymptomatic and 30 with HAM/TSP, according to neurological evaluation) and 60 not-infected, who were matched for gender and age with the HTLV-1-infected group. All participants underwent an interview about general health status and otoneurological manifestations. The participants who complained of dizziness, tinnitus or hearing loss were evaluated by the otolaryngologist and submitted to specific tests to define the diagnosis. The vestibular-evoked myogenic potential (VEMP) was performed to test the function of the vestibulospinal tract in those that complained of dizziness. The frequency of otoneurologic manifestations was then compared. RESULT: The complaint of hearing loss (p=0.506) and tinnitus (p=0.498) were similar. Dizziness predominated in the HAM/TSP group (p=0,002). Instability was the most frequent type of dizziness among the individuals infected by HTLV-1 (p=0,006). VEMP was altered in 43% of the asymptomatic carries and in 85% of the individuals with HAM/TSP. CONCLUSION: Dizziness as the sensation of instability was found to be a clinical manifestation of HAM/TSP. Vestibulospinal tract injury was demonstrated through VEMP to occur more frequently in HAM/TSP. Possibly, the complaint of dizziness in asymptomatic carriers may be an early indicator of progression to HAM/TSP.